Effect of the previous crop and of soil compaction on macronutrient uptake by soybean - Silva, R. H. de (2001)
The effect of seven species cropped just before soybean, as well as the effect of soil compaction on macronutrient uptake by soybean were evaluated. The experiment was conducted in pots containing a Red Latosol (Acrortox, loamy sand), and the pots had a layer 3.5 cm thick and 15 cm deep compacted to 1. 12, 1,36 and 1.60 Mg m(-3). Before soybean, the pots were cropped to black oat, pigeon pea, pearl millet, black mucuna, soybean, grain sorghum and lupin, plus a treatment without plants. These species were grown for 37 to 39 days, when they were cut at soil level, pricked into particles of approximately 3 cm length, and left on the soil surface for 40 days, After this, soybean was planted in the pots and grown for 28 days after plant emergence. The shoot dry matter weight, concentration and accumulation were evaluated. The subsoil compaction decreased the nutrition of soybean. The nutrition of soybean is benefited when in sequence to soil cover crops. The soil without plants is not recommended as well as method to reduce the effects of the soil compaction.